استخدام المصفوفات في جدولة الاعمال التي تتطلب مرورا متسلسلا على الاالات "خوارزمية مقترحة" (مجلة المنصور, 2023)
استخدام المصفوفات في جدولة الاعمال التي تتطلب مرورا متسلسلا على الاالات "خوارزمية مقترحة"